2020
DOI: 10.3390/cancers12082306
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Primary Tumor Resection in Colorectal Cancer Patients with Asymptomatic, Synchronous, Unresectable Metastasis: A Multicenter Randomized Controlled Trial

Abstract: We aimed to assess the survival benefits of primary tumor resection (PTR) followed by chemotherapy in patients with asymptomatic stage IV colorectal cancer with asymptomatic, synchronous, unresectable metastases compared to those of upfront chemotherapy alone. This was an open-label, prospective, randomized controlled trial (ClnicalTrials.gov Identifier: NCT01978249). From May 2013 to April 2016, 48 patients (PTR, n = 26; upfront chemotherapy, n = 22) diagnosed with asymptomatic colorectal cancer with unresect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 30 publications
(37 reference statements)
4
36
0
4
Order By: Relevance
“…While PTR followed by chemotherapy resulted in better two-year cancer-specific survival than upfront chemotherapy, the improvement in the two-year OS was not significant. 37 Our multidisciplinary team discussed the two randomized trials with opposite opinions (JCOG1007 and PTR Trial) and believed that although the sample size was small, it was very influential. In the light of previous retrospective studies and the experience of our center (the median overall survival: PTR vs CTX, 18.0 months vs 15.0 months, P=0.006), we believed that at present we should be more cautious about whether to recommend PTR, but at the same time, we have more expectations for randomized controlled trials of patients with stage IV incurable colorectal cancer, such as CAIRO-4 (NCT01606098), SYNCHRONOUS (ISRCTN30964555), CLIMAT (NCT02363049), CCRe-IV (NCT02015923), China multicenter (NCT0214978424), GRECCAR 8 (NCT02314182) and hope that when the comprehensive results of these trials are reported in the near future, the role of PTR will be better defined.…”
Section: Discussionmentioning
confidence: 99%
“…While PTR followed by chemotherapy resulted in better two-year cancer-specific survival than upfront chemotherapy, the improvement in the two-year OS was not significant. 37 Our multidisciplinary team discussed the two randomized trials with opposite opinions (JCOG1007 and PTR Trial) and believed that although the sample size was small, it was very influential. In the light of previous retrospective studies and the experience of our center (the median overall survival: PTR vs CTX, 18.0 months vs 15.0 months, P=0.006), we believed that at present we should be more cautious about whether to recommend PTR, but at the same time, we have more expectations for randomized controlled trials of patients with stage IV incurable colorectal cancer, such as CAIRO-4 (NCT01606098), SYNCHRONOUS (ISRCTN30964555), CLIMAT (NCT02363049), CCRe-IV (NCT02015923), China multicenter (NCT0214978424), GRECCAR 8 (NCT02314182) and hope that when the comprehensive results of these trials are reported in the near future, the role of PTR will be better defined.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a prospective randomized trial with a very small sample size (48) of participants was reported, and the results showed that, compared with chemotherapy alone, PTR followed by chemotherapy improved the 2-year cancer-specific survival of patients with asymptomatic stage IV CRC, although no statistical difference was obtained, which might due to the limited patients (14). However, different results were reported in another prospective randomized trial (JCOG1007 study) with a larger sample size of participants which enrolled 165 patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, there were 2 reports of prospective randomized clinical trials to compare the effects of PTR followed by chemotherapy with chemotherapy alone, but the results in these 2 studies are also different and controversial (14,15). We also performed this randomized phase II trial from 2015 in colon cancer patients with unresectable metastases, but the design of our study was different with the two reported studies, as we enrolled patients and gave them induction chemotherapy for 3 months, excluded patients with chemotherapy failure whose prognosis was always poor, and then randomly divided them into PTR group and chemotherapy group to compare the effects of induction chemotherapy followed by PTR and chemotherapy alone and determine the value of PTR after induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, age, histological type, CEA and chemotherapy were also determined as important factors for CSS of T1N0M1 patients, which have been linked with considerable importance in predicting survival of CC patients in recent years. [24][25][26] Therefore, a nomogram was built to determine cancer-specific…”
Section: Discussionmentioning
confidence: 99%